Southern Semitic and Arabic dialects of the south-western Arabian Peninsula - Watson, Janet C.E. (Proceedings of the Seminar for Arabian Studies, 2014)
In this paper I examine a selection of key phonetic, phonological, and morphological commonalities exhibited by Ancient South Arabian (ASA), Modern South Arabian (MSAL), and Arabic varieties spoken in western Yemen, south-western Saudi Arabia, and Oman, drawing relevant comparisons with Ethio-Semitic. This study shows a wide range of shared and overlapping features between the so-called southern Arabic varieties examined and the non-Arabic varieties, suggesting a need to realign the position of southern Arabic in the Semitic language family.